Open-air spray plasma deposited UV-absorbing nanocomposite coatings. Issue 30 (19th July 2018) - Ding, Yichuan; Dong, Siming; Hilt, Florian; Dauskardt, Reinhold H.
Abstract : Mechanically robust UV-absorbing nanocomposite coatings with good nanoparticle uniformity and dispersity were deposited using a versatile dual-source deposition method. Abstract : We demonstrate the deposition of mechanically robust UV-absorbing nanocomposite coatings with a newly developed dual-source deposition method involving ultrasonic spraying and open-air plasma deposition. Nanoparticles and the coating matrix are independently deposited which eliminates difficulties associated with preparing composites with high mass fraction of well-dispersed nanoparticles in the matrix. Nanocomposite coatings containing different concentrations of silica, ceria, and both titania and ceria nanoparticles were successfully deposited with good nanoparticle dispersity, high transparency over the visible range, effective absorption in the UV wavelength, and enhanced mechanical properties. Moreover, films were successfully deposited on several substrates including polycarbonate to demonstrate the low processing temperature of this dual-source deposition method. Coatings with different nanoparticle concentrations and film thicknesses were systematically studied in terms of their surface morphology, optical properties and mechanical properties. Accelerated photostability testing of the UV-absorbing nanocomposites demonstrates significantly enhanced performance compared to existing coatings with either a polymeric matrix or organic UV-absorbers.